2021
DOI: 10.4028/www.scientific.net/msf.1035.608
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Content on the Micromorphology, Microhardness and Micro Frictional Resistance of Co-Ni-Graphene Composite Coating

Abstract: In order to obtain the alloy composite material with high hardness, good anti-friction property and low friction coefficient, the electrodeposition technology was used to prepare nanocrystalline Co-Ni-graphene composite coating on the surface of low carbon steel by means of ultrasonic dispersion combined with mechanical agitation. The influence of graphene content in electrolyte on composite coating was studied. The surface microstructure, composition, phase structure, micro-hardness and micro-wear properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This technique promotes the refinement of crystal grain. 5 Gao et al 6 conducted a study where they prepared a Co–Ni/graphene composite coating on a copper crystallizer substrate. By adjusting the percentage of Co content in the coating, they found that high Co composite coatings exhibited excellent hardness and good wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This technique promotes the refinement of crystal grain. 5 Gao et al 6 conducted a study where they prepared a Co–Ni/graphene composite coating on a copper crystallizer substrate. By adjusting the percentage of Co content in the coating, they found that high Co composite coatings exhibited excellent hardness and good wear resistance.…”
Section: Introductionmentioning
confidence: 99%